Transcriptomic and biochemical insights into key gene networks driving bulbil development of Pinellia ternata (Thunb.) Breit - Xiwei Jia; Xijia Jiu; Yuan Liu; Chao Guo; Dong Liu; Xin Zhao; Honggang Chen; Tao Du (PLoS ONE, 2025)
In this study, we explored the developmental characteristics of Pinellia ternate bulbils as well as the key gene networks driving the development of bulbils. Based on physiological and biochemical reactions as well as transcriptome technology, this study determined the content of endogenous metabolites and related enzyme activities during the five growth stages of the bulbils, obtained the transcriptome information of all samples. The results showed that the contents of sucrose and starch increased significantly in the ZY_2 and ZY_4 stages, and the changes in the activities of SPS, SuSy, and SS were basically consistent with the changing characteristics of sucrose and starch content. The contents of ABA and JA generally showed an increasing trend from ZY_1 to ZY_4, while the content of IAA was significantly higher only in ZY_1 and ZY_4 stages compared to other stages. In order to get more bioinformatic support for these results, RNA-Seq analysis was performed. There were 12 key enzyme genes differentially expressed in the sucrose-starch metabolic pathway, and 14 enzyme genes differentially expressed in the above-mentioned endogenous hormone metabolic pathway. Their expression characteristics well supported the measurement results of physiological and biochemical substances. Our results showed that ZY_2 and ZY_4 stages are the critical periods for the accumulation of sucrose and starch in the bulbils. JA has an important role in the whole development process of bulbils, which may enhance the adaptability of the bulbils to the environment in the transition process from the tender to the mature tissues. The low concentration of GA was beneficial to the normal development of the bulbils. IAA may have a strong regulatory role in the initial formation stage of the bulbils, which is beneficial to their tissue differentiation. In addition, four core transcripts involved in the bulbils development process were screened using WGCNA. This study provides an information source for analyzing the molecular mechanism of bulbils growth and development, and also helps to address the lack of genetic information in non-model plant species.